Distribution of alleles related to grain weight and quality in Moroccan and North American wheat landraces and cultivars - Chegdali, Youssef; Ouabbou, Hassan; Essamadi, Abdelkhalid; Sahri, Ali; Núñez Ríos, Claudia; Dreisigacker, Susanne; Guzmán García, Carlos (Springer, 2022)
Combining improved grain yield and end-product quality in durum wheat has become an essential priority for Moroccan breeding programs due to their significant effect on the country's agricultural economy and social system. Landraces and cultivars of distinct germplasm pools constitute an untapped source of genetic variation for durum wheat improvement. To this end, a mixture of genotypes consisting of 35 landraces (LAN), 20 North American cultivars (NAC) and 10 Moroccan cultivars (MC), was evaluated using grain weight and grain size parameters, quality characteristics, and 21 functional molecular markers. Significant genetic variability was revealed between the genotypes. According to observed means across traits, MC showed the best grain characteristics, followed by NAC, and LAN. However, NAC showed overall better physiochemical characteristics. Genetic diversity applying quality trait-based markers increased from LAN to advanced cultivars. Favorable alleles Lpx-B1.1b (Lpx-B1.1), Hap-4A-T (TaCwi-4A), TaGS5-A1b (TaGS5-A1) were predominant in NAC. Unfavorable alleles, namely Psy1-B1a (Psy1-B1), Psy-B1a or b (Psy-B1), Lox-B1a (Lox-B1), Hap- 4A-C (TaCwi-4A), TaGS5-A1a (TaGS5-A1), TaTGW6-b (TGW6-4A), Hap-L (TaSus2), and TaTGW6-A1b (TGW6), were most frequent or even omniprevalent in all genotypes. This work can up open new avenues for the development of new varieties allying yield and grain quality by introducing suitable genotypes and favorable alleles into Moroccan national breeding programs.